Effect of Oral Alkali Supplementation on Progression of Chronic Kidney Disease - Gaggl, Martina; Sliber, Christopher; Sunder-Plassmann, Gere (Current Hypertension Reviews, 2014)
Metabolic acidosis is a frequent but asymptomatic complication in chronic kidney disease (CKD). In early stages of CKD acidosis is limited to the renal tissue and progresses to reduced serum bicarbonate levels. Reduced renal tissue pH and increased ammoniagenesis are the key mechanisms of the kidney to enhance acid excretion to the urine. The expressed protein patterns in the proximal tubular epithelial cells change remarkably, the proximal convoluted tubule develops hypertrophy, and an intra-renal enhanced renin-angiotensin-system leads to interstitial fibrosis. Since nephrons are numerically reduced in CKD each remaining functional unit has to progressively increase these mechanisms to keep up the equilibrium. The adverse effects of chronic metabolic acidosis include aside from acceleration of progression of kidney disease, the development or exacerbation of bone disease, increased degradation of muscle with muscle wasting, enhanced protein degradation and inflammation. Genome wide association studies demonstrated that tubular acid-base transporters are involved in the development of arterial hypertension. Several retrospective analyses have indicated that low serum bicarbonate predicts death in cohorts with CKD and cardiovascular disease. All studies confirmed a U-shaped association of mortality and serum bicarbonate, indicating that both, acidosis and alkalosis are associated with increased mortality. Randomized controlled trials showed that base substitution, either by modification of the diet or by simply adding alkalizing agents, might halt the decline of kidney function in subjects with CKD. In 2012 a meta-analysis concluded that alkali therapy might provide a long-term favorable effect on renal function in patients with CKD.
Keywords: alkali